Improving the Quality and Luminescence Performance of All‐Inorganic Perovskite Nanomaterials for Light‐Emitting Devices by Surface Engineering. Issue 26 (20th May 2020) - Shen, Zhaohui; Zhao, Suling; Song, Dandan; Xu, Zheng; Qiao, Bo; Song, Pengjie; Bai, Qiongyu; Cao, Jingyue; Zhang, Gaoqian; Swelm, Wageh
Abstract: Lead halide perovskites and their applications in the optoelectronic field have garnered intensive interest over the years. Inorganic perovskites (IHP), though a novel class of material, are considered as one of the most promising optoelectronic materials. These materials are widely used in detectors, solar cells, and other devices, owing to their excellent charge‐transport properties, high defect tolerance, composition‐ and size‐dependent luminescence, narrow emission, and high photoluminescence quantum yield. In recent years, numerous encouraging achievements have been realized, especially in the research of CsPbX3 (X = Cl, Br, I) nanocrystals (NCs) and surface engineering. Therefore, it is necessary to summarize the principles and effects of these surface engineering optimization methods. It is also important to scientifically guide the applications and promote the development of perovskites more efficiently. Herein, the principles of surface ligands are reviewed, and various surface treatment methods used in CsPbX3 NCs as well as quantum‐dot light‐emitting diodes are presented. Finally, a brief outlook on CsPbX3 NC surface engineering is offered, illustrating the present challenges and the direction in which future investigations are intended to obtain high‐quality CsPbX3 NCs that can be utilized in more applications. Abstract : Surface engineering could influence the performance of inorganic perovskite nanomaterials and devices. Herein, common synthesis methods of perovskite nanomaterials and the working principles and effects of common ligands are reviewed, and the surface treatment methods used to improve the performance of perovskite quantum dot light emitting diodes are introduced .